The Effect of Related and Unrelated Diversifications of Capital Structure Policy: Evidence from Indonesia - RATNA WARDHANI; ADE SOBRINA HASIBUAN (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to analyze the role of related and unrelated diversification of listed firms in Indonesia on capital structure decision, using 78 Indonesian companies listed on the Indonesian Stock Exchange between 2002 and 2007 as samples and panel data methodology. The result shows that, in general, diversification positively affects firms’ leverage. This result also applies to unrelated diversification strategy, where firms with unrelated diversification strategy are inclined to see an increase in the level of firm leverage; in other words, unrelated diversification has a positive effect on debt as a source of finance. Therefore, capital structure decisions of unrelated diversified firms seem to be strictly aimed at reaching their optimal debt level target and are consistent with the static trade off hypothesis. However the relation between related diversification strategy and a firm’s capital structure cannot be proven in this study due to the possibility that such strategy will require less investment costs.